SISTEM PENETAPAN NILAI JUAL OBJEK PAJAK (NJOP) TANAH, DALAM PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) MENURUT UNDANG-UNDANG PAJAK DAERAH DAN RETRIBUSI DAERAH NO. 28 TAHUN 2009 DI SAMARINDA - MISTURIYANI, SRI (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTÂ In the management of land and rural and urban land tax (PBB-P2) in addition to the determination of tax rates, the Regional Government also has the authority to determine the size of NJOP per square meter land based on the assessment results. Land valuation is done by market data comparison method and done in bulk. Appropriation of NJOP of land can reasonably be carried out if the assessment is done objectively and the data obtained may reflect the fair market price of the land at the assessment site in the year of appraisal.The method used in this research is (1) normative juridical by collecting data from books, laws, internet. and (2) juridical sociology that goes directly to the field by interview and question and answer to BAPENDA officer as resource person.From research conducted at the Office of BAPENDA of Samarinda City, the determination of NJOP of land against PBB-P2 according to Law no. 28 of 2009 on Regional Taxes and Levies, the determination of NJOP is done by comparison of the price of other similar objects, the new acquisition value by calculating all the costs incurred to obtain the object of the tax when the appraisal is done, the substitute selling value based on the result of the tax object production called the income approach.